Arthropathy in dermatology: A comprehensive review - Soumya Jagadeesan; Padmanabha Shenoy (Wolters Kluwer Medknow Publications, 2017)
Dermatology and rheumatology are two specialties that deal with significant overlap. In this context, it is important that the dermatologists acquaint themselves with conditions presenting with arthropathy. As the first step, it is essential to know whether the origin of musculoskeletal symptom is articular or extra-articular; inflammatory or noninflammatory; acute or chronic; oligo- or poly-articular. This will help in narrowing down the differential diagnoses as well as in better correlation with the cutaneous symptoms. In this review, we discuss the skin and articular manifestations of common inflammatory and noninflammatory arthropathies including rheumatoid arthritis, spondyloarthropathies, connective tissue disorders, vasculitis, crystal arthropathies, infective arthritis, arthritis associated with degenerative, endocrine and metabolic conditions, etc. We have also added a section on the common cutaneous features associated with the treatment of rheumatologic diseases. A basic understanding of the joint pathologies and associated skin changes will help a long way in the better management of these conditions.